Application of high performance liquid chromatography coupled with ultraviolet spectroscopy and electrospray mass spectrometry to the characterisation of ellagitannins from Terminalia macroptera roots - Silva, O (2015)
Purpose. Terminalia macroptera roots are used in Guinea-Bissau and other West African countries to treat infectious diseases like gonorrhoea. Previous work showed an ethanol extract of T. macroptera roots (T) to have an in vitro antimicrobial profile against Neisseria gonarrhoae (including resistant strains) and enteropathogenic agents. The most active fractions of this extract were identified as the diethyl ether (T2) and water (T5) fractions. The aim of the present study was the identification of major compounds present in T and simultaneously in T2 or T5. Methods. The T extract and T2 and T5 fractions were analysed by high performance liquid chromatography coupled with ultraviolet photodiode array (LC-UV) spectroscopy and electrospray ionization mass spectrometry (E-MS). These analyses indicated the presence of ellagitannin derivatives. In order to confirm the identities of the detected compounds, they were isolated from T2 and T5 by preparative chromatographic techniques and identified by spectroscopic methods including tandem mass spectrometry. Results. By using LC-UV-ES-MS, four major compounds (ellagic acid, gallic acid, punicalagin, terchebulin) could be identified in the T extract. Three other compounds (3,3'di-O-methylellagic acid, 3,4,3',4'-tetra-O-methylellagic acid, terflavin A) were also isolated and identified. Conclusions. LC-UV-ES-MS is a useful technique for the analysis of mixtures containing ellagitannins.